Dye-functionalized graphene/polyaniline nanocomposite as an electrode for efficient electrochemical supercapacitor. (12th August 2015) - Lü, Qiu-Feng; Chen, Guo; Lin, Ting-Ting; Yu, Yan
Abstract: Three dye-functionalized graphene oxide/polyaniline (GAP) composites were first prepared by optimizing acid blue 74 (AB74) feed content, and then dye-functionalized graphene/polyaniline (rGAP) nanocomposites were obtained from the GAP composites through reducing and re-protonating treatments. The AB74 dye molecules with negatively charged sulfonic groups can effectively prevent aggregation of graphene sheets during the reduction process of graphene oxide, and can be used as a bridge to attach polyaniline nanorods via π–π conjunction and electrostatic attraction. Furthermore, when rGAP5 (the AB74 feed content of 5 wt.%) was used as a supercapacitor electrode material, it achieved a high specific capacitance of 579 F g −1 at a current density of 0.5 A g −1, good cycling stability and rate capacity.